Metallic nanosculptured thin films for biosensing applications using surface Plasmon resonance and enhanced spectroscopies - Shalabney, Atef (2013)
Metallic nanosculptured thin films are made of nanorods in different shapes prepared by means of the oblique angle deposition technique. Assessment of these films for biosensing and molecular detection has been investigated by our group recently using surface Plasmon resonance (SPR), surface enhanced fluorescence (SEF), and surface enhanced Raman scattering (SERS). Using columnar thin film (CTF) as the transducer layer in SPR sensors enhances both the angular and spectral sensitivity of the sensor. Sculptured thin films (STFs) made of different materials, shapes, sizes, orientations, porosities, and deposited on different substrates were examined as SEF and SERS detection platforms. The optimal features of STFs were examined to obtain the highest enhancement of SERS and SEF. The potential of these films for biosensing and bimolecular detection was demonstrated. Stability of the films was noticed over a period of one year without significant degradation.